Hospital transition care for the elderly: an integrative review - Tânia Maria de Oliva Menezes; Ana Luíza Barreto de Oliveira; Lucivalda Barbosa Santos; Raniele Araújo de Freitas; Larissa Chaves Pedreira; Sylvia Maria Cardoso Bastos Veras (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to identify evidence of scientific production on hospital transition care provided to the elderly. Method: an integrative review, with publications search in the MEDLINE, PubMed, LILACS, BDENF, Index Psychology and SciELO databases, with keywords and Mesh terms: elderly, hospitalization, patient discharge, health of the elderly, and transitional care, between 2013 and 2017 in English, Portuguese and Spanish. The 14 selected articles analysis was carried out through exploratory and critical reading of titles, abstracts and results of the researches. Results: transitional care can prevent re-hospitalizations as they enable rehabilitation, promotion and cure of illnesses in the elderly. Final considerations: transitional care implies the improvement of the quality of life of the elderly person, requiring skilled health professionals who involve the family through accessible communication.